WORKING WITH DATA TABLES AND GRAPHS AT PRIMARY SCHOOL - Papancheva, Rumyana Y (Journal of process management and new technologies, 2017)
The article presents a model for developing data handling competencies at Primary school. The work is part of a larger research aiming at forming basic statistic literacy at early ages. Data analysis knowledge and skills are important part for the nowadays person. At Primary school, some basic skills for data handling must be developed. Working with data structured in tables and presented by graphs corresponds with the process of developing students’ digital skills. Experimental work was done at third grade of primary school in equipped with contemporary technologies learning environment. Some example tasks are presented and the results from the experimental work are analysed.